Etika Dan Tanggung Jawab Sosial - Idrus Usu (JURNAL LEGALITAS, 2009)
Basically present business will not be endless otherwise is accompanied with ethics. This thing of course very far diffired from tending to industry era concept that permits all ways, pursues maximum benefits without bothering ethics and others importance, environment and generation a period of coming. Business ethics is study majored about wrong and correct morale. This study concentrates on morale standard as applied in policy, institution, and behavior of business. Whereas social responsibility is processing social interaction between the componies and public. Public claim and development of democracy and rapid of globalization current and free market, causing peeps out awareness from industrial world about the importance of executing company social responsibility (Company social responsibility). Kata Kunci: Etika, Tanggung Jawab Sosial, Bisnis, Perusahaan, Manajemen.